Delivering outpatient virtual clinics during the COVID-19 pandemic: early evaluation of clinicians' experiences. Issue 1 (7th January 2022) - Vas, Venessa; North, Shirley; Rua, Tiago; Chilton, Daniella; Cashman, Michaela; Malhotra, Bharti; Garrood, Toby
Abstract : Background: The COVID-19 pandemic has put health systems across the world under significant pressure. In March 2020, a national directive was issued by the National Health Service (NHS) England instructing trusts to scale back face-to-face outpatient appointments, and rapidly implement virtual clinics. Methods: A multidisciplinary team of change managers, analysts and clinicians were assembled to evaluate initial implementation of virtual clinics at Guy's and St Thomas' NHS Foundation Trust. In-depth interviews were conducted with clinicians who have delivered virtual clinics during the pandemic. An inductive thematic approach was used to analyse clinicians' early experiences and identify enablers for longer term sustainability. Results: Ninety-five clinicians from specialist services across the trust were interviewed between April and May 2020 to reflect on their experiences of delivering virtual clinics during Wave I COVID-19. Key reflections include the perceived benefits of virtual consultations to patients and clinicians; the limitations of virtual consultations compared with face-to-face consultations; and the key enablers that would optimise and sustain the delivery of virtual pathways longer term. Conclusions: In response to the pandemic, outpatient services across the trust were rapidly redesigned and virtual clinics implemented. As a result, services have been able to sustain some level of service delivery. However, clinicians have identified challenges in delivering this model of care and highlighted enablers needed to sustaining the delivery of virtual clinics longer term, such as patient access to diagnostic tests and investigations closer to home.